2011
DOI: 10.1016/j.cell.2011.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Metastasis: Molecular Insights and Evolving Paradigms

Abstract: Metastases represent the end-products of a multi-step cell-biological process termed the invasion-metastasis cascade, which involves dissemination of cancer cells to anatomically distant organ sites and their subsequent adaptation to foreign tissue microenvironments. Each of these events is driven by (1) acquisition of genetic and/or epigenetic alterations within tumor cells and (2) co-option of non-neoplastic stromal cells, which together endow incipient metastatic cells with traits needed to generate macrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
2,840
1
22

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,285 publications
(2,967 citation statements)
references
References 110 publications
22
2,840
1
22
Order By: Relevance
“…43 While a role for Arf6 in tumor metastasis had been appreciated for some time, the earliest report of BRAG2 involvement in metastasis came from studies by Sabe and colleagues, who showed that knockdown of BRAG2 potently inhibited the migration of breast cancer (MDA-MB-231) cells through matrigel. 7 Moreover, upon EGF stimulation of these cells BRAG2 bound directly to the EGF receptor through association of its PH domain with phosphorylated tyrosine residues (Y1068/Y1086) in the receptor.…”
Section: Brag Proteins In Cancer Metastasismentioning
confidence: 99%
“…43 While a role for Arf6 in tumor metastasis had been appreciated for some time, the earliest report of BRAG2 involvement in metastasis came from studies by Sabe and colleagues, who showed that knockdown of BRAG2 potently inhibited the migration of breast cancer (MDA-MB-231) cells through matrigel. 7 Moreover, upon EGF stimulation of these cells BRAG2 bound directly to the EGF receptor through association of its PH domain with phosphorylated tyrosine residues (Y1068/Y1086) in the receptor.…”
Section: Brag Proteins In Cancer Metastasismentioning
confidence: 99%
“…3 Each of these events is classically driven by the acquisition of genetic and/or epigenetic traits in tumor cells and the cooperation of nonneoplastic stromal cells. Increased or decreased expression of several genes in tumors has been found to be correlated with metastasis.…”
mentioning
confidence: 99%
“…Increased or decreased expression of several genes in tumors has been found to be correlated with metastasis. 3 However, specific gene alterations that drive NSCLC metastasis remain largely elusive.…”
mentioning
confidence: 99%
“…The metastatic process comprises a complex sequence of events including invasion of the surrounding matrix, intravasation to blood or lymphatic circulation, anchorage independent survival, and extravasation into foreign tissues (1). This multistep cascade is driven by genetic and epigenetic alterations that induce motility, invasiveness, resistance to apoptosis/anoikis, and self-renewal potential in a subpopulation of tumor cells (2,3).…”
Section: Introductionmentioning
confidence: 99%